Food Familiarity Influence Food Preferences Among High School Student in Ogan Ilir District (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
Food preferences are the level of the likes and dislikes of food, and these preferences will affect food consumption that represents the selection of a person’s diet frequency, nutrient intake and dietary adequacy. Based on previous research, food preferences in adolescents as a whole are not in line with a healthy diet, and food preferences of adolescents are a critical point that determines food preferences of adults. The purpose of this study is to analyze food preferences of adolescence and the various factors which influence it. This research was an analytical study with cross-sectional design. The samples were High School students at Senior High School 1 Inderalaya and Senior High School 1 South Inderalaya with the total number 167 ,and people. Samples were taken by simple random sampling. The food preferences data were obtained by using food checklist and hedonic scale of 1-5. Procedure of data analysis used was univariate and bivariate analysis with chi-square. Bivariate analysis showed that 61.1% of the respondent have good food preferences. Analysis of the relationship between variables showed a significant relationship between food familiarity with food preferences (p-value = 0.000) with PR= 3.459 (95% CI: 2.284-5.239) while other variables Such as the influence of peers, food neophobia, body image perception, gender, allowance, nutritional knowledge, and food taboo did not have any relationship with food preferences. The higher someone’s food familiarity level is, the higher the preference is. We suggest the school to increase food preferences for students to learn about a variety of nutritious foods balanced through a variety of activities, such as scientific discussions, a competition to create a menu of balanced nutrition, healthy food promotion